POLA SEBARAN POPULASI AREN (Arenga pinnata) BERDASARKAN KELAS PERTUMBUHAN DI DESA SANGTANDUNG KECAMATAN WALENRANG UTARA KABUPATEN LUWU - Witno Witno; Hadijah Azis Karim; Megawati Megawati (Universitas Andi Djemma Palopo, 2021)
Aren (Arenga pinnata) is a type of palm where almost all of its parts can be utilized, starting from the roots, stems, leaves, flowers, and fruit. Based on the growth rate of sugar palm can show the pattern of distribution using the Morisita index formula. The distribution pattern is a series that has settled on a symptom itself between individuals, which can be divided into three, namely uniform (regular), random (random), and clustered (clustered). This study aims to determine the distribution pattern of the sugar palm (Arenga pinnata) population based on the growth rate. This research was carried out in Sangtandung Village in July 2021. The data collection method used a purposive sampling technique by placing plots in an area with a sugar palm population following the river body 200 meters long. The distribution pattern of sugar palm based on the growth rate was analyzed using the Morisita index formula. Based on the Morishita index, the study results obtained a pattern of palm sugar distribution based on the growth rate, namely seedlings, saplings, trees with clustered patterns, and poles with uniform patterns.